Medicarpin Increases Antioxidant Genes by Inducing NRF2 Transcriptional Level in HeLa Cells - Jung-Hwan Kim; Dong-Min Kang; Young-Jin Cho; Jin-Won Hyun; Mi-Jeong Ahn (MDPI AG, 2022)
The nuclear factor erythroid-derived 2-related factor 2 (NRF2) plays a pivotal role in the regulation of genes involved in oxidative stress and drug detoxification. Therefore, it is important to find NRF2 inducers to protect cells from excessive oxidative damage. Here, we investigated the effect of medicarpin isolated from the root of Robinia pseudoacacia L. on the activity of NRF2 in HeLa cells. Medicarpin significantly induced the antioxidant response elements (ARE)-luciferase activity in a concentration-dependent manner. Furthermore, medicarpin not only induced HO-1, GCLC, and NQO1 mRNA by translocating NRF2 to the nucleus but also induced the mRNA level of NRF2. To verify the NRF2 induction mechanism by medicarpin, ~2 kb of NRF2 promoter-luciferase assay was executed. As a result, medicarpin significantly induced NRF2-luciferase activity. Moreover, medicarpin strongly inhibited the ubiquitin-dependent proteasomal degradation of NRF2. Thus, medicarpin might protect cells by promoting the NRF2 transcriptional activity.